UMPSA hosts 8th International Conference on Mechanical Engineering Research (ICMER 2025) in Kuala Lumpur - Muhamad, Mat Noor (UMPSA, 2025)
KUALA LUMPUR, 6 August 2025 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) officially opened the 8th International Conference on Mechanical Engineering Research (ICMER 2025) at The Pearl Hotel, Kuala Lumpur, from 6 to 7 August 2025.